Ability Emotional Intelligence, Attachment Models, and Reflective Functioning - Rosso, Anna Maria (Frontiers in Psychology, 2022)
Previous studies have reported a significant positive association between ability emotional intelligence (EI) and attachment security. However, these studies may, to some extent, be misleading because they relied on self-report measures of attachment security. Furthermore, to our knowledge, no study has yet investigated the relationship between ability EI and mentalization, operazionalized as reflective functioning (RF), although EI and RF were assumed to be “conceptual cousins.” In an attempt to overcome some of the limitations of the previous research, the current study investigated the relationships between ability EI, attachment security, and mentalization measured via the Adult Attachment Interview (AAI). Ninety-three volunteer participants from an Italian community population (49.5% males), aged from 27 to 55 years (M = 39.44; SD = 6.84), took part in the study. Significant positive correlations were found between ability EI, attachment security, and RF. The results shed some light on the relationship between different attachment strategies and ability EI. Hyperactivating attachment strategies correlated negatively with ability EI, while the correlation between ability EI and attachment deactivating strategies depend on which defensive strategy is used: avoiding the painful emotional contact with the memory of unpleasant childhood attachment experiences positively correlated with experiential EI, whilst the resort to derogation of the attachment needs correlated with impairment in EI. Findings from the current study suggest that future studies in developmental psychology are needed to investigate the development of the ability EI in relation to the quality of the attachment models more in-depth.